2013
DOI: 10.1089/aid.2012.0232
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Fasting Increases Serum Concentrations of Bilirubin in Patients Receiving Atazanavir: Results from a Pilot Study

Abstract: Unconjugated hyperbilirubinemia resulting from therapy with atazanavir is physiologically related to hyperbilirubinemia in Gilbert's syndrome (GS). In patients with GS, changes in diet have a significant impact on bilirubinemia. Our aim was to investigate whether changes in diet affect the level of serum bilirubin in patients receiving atazanavir. Thirty patients on stable therapy with ritonavir-boosted atazanavir without evidence of GS were enrolled. Hemolysis and chronic hepatitis were excluded. After a base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A study by Lopardo and colleagues in 2013 showed that fasting increases serum concentrations of Bilirubin in patients receiving atazanavir therapy for HIV 5. However, it should be noted that food affects atazanavir levels and the drug itself causes hyperbilirubinaemia 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Lopardo and colleagues in 2013 showed that fasting increases serum concentrations of Bilirubin in patients receiving atazanavir therapy for HIV 5. However, it should be noted that food affects atazanavir levels and the drug itself causes hyperbilirubinaemia 5.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lopardo and colleagues in 2013 showed that fasting increases serum concentrations of Bilirubin in patients receiving atazanavir therapy for HIV 5. However, it should be noted that food affects atazanavir levels and the drug itself causes hyperbilirubinaemia 5. Lopardo and colleagues propose that an increased hepatic uptake of non-esterified fatty acids interferes with the hepatic clearance of bilirubin and thus contributes to the unconjugated hyperbilirubinaemia of fasting 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation